Dimethyl phthalate destroys the cell membrane structural integrity of Pseudomonas fluorescens - Chen, Wenjing; Guo, Ruxin; Wang, Zhigang; Xu, Weihui; Hu, Yunlong (Frontiers in Microbiology, 2022)
A gram-negative bacteria (Pseudomonas fluorescens) was exposed to different concentrations (0, 20 and 40 mg/L) of dimethyl phthalate (DMP) for 8 h, and then fourier transform infrared spectroscopy analysis, lipopolysaccharide content detection, analysis of fatty acids, calcein release test, proteomics, non-targeted metabolomics and enzyme activity assays were used to evaluate the toxicological effect of DMP on P. fluorescens. The results showed that DMP exposure caused an increase unsaturated fatty acids/saturated fatty acids (UFA/SFA) ratio and in the release of lipopolysaccharides (LPS) from the cell outer membrane of P. fluorescens. Moreover, DMP regulated the abundances of phosphatidyl ethanolamine (PE) and phosphatidyl glycerol (PG) of P. fluorescens and induced dye leakage from artificial membrane. Additionally, excessive reactive oxygen species (ROS), malondialdehyde (MDA) and changes in antioxidant enzymes (i.e., CAT and SOD) activities, as well as down-regulation of methyl-accepting chemotactic protein, inhibition of Ca2+-Mg2+-ATPase and Na+/K+-ATPase activities in P. fluorescens which were induced by the DMP. In summary, DMP could disrupt the lipid asymmetry of the outer membrane, increase the fluidity of the cell membrane and destroy the integrity of the cell membrane of P. fluorescens. DMP also caused lipid peroxidation, oxidative stress, reduced chemotaxis, potassium imbalance and impaired signal reception.